Suppression of Cisplatin-Induced Vomiting by Cannabis sativa in Pigeons: Neurochemical Evidences - Ullah, Ihsan; Subhan, Fazal; Alam, Javaid; Shahid, Muhammad; Ayaz, Muhammad (Frontiers in Pharmacology, 2018)
Cannabis sativa (CS, family Cannabinaceae) has been reported for its anti-emetic activity against cancer chemotherapy-induced emesis in animal models and in clinics. The current study was designed to investigate CS for potential effectiveness to attenuate cisplatin-induced vomiting in healthy pigeons and to study the impact on neurotransmitters involved centrally and peripherally in the act of vomiting. High-performance liquid chromatography system coupled with electrochemical detector was used for the quantification of neurotransmitters 5-hydroxytryptamine (5HT), dopamine (DA) and their metabolites; Di-hydroxy Phenyl Acetic acid (Dopac), Homovanillic acid (HVA), and 5-hydroxy indole acetic acid (5HIAA) centrally in specific brain areas (area postrema and brain stem) while, peripherally in small intestine. Cisplatin (7 mg/kg i.v.) induce emesis without lethality across the 24 h observation period. CS hexane fraction (CS-HexFr; 10 mg/kg) attenuated cisplatin-induced emesis ∼ 65.85% (P < 0.05); the reference anti-emetic drug, metoclopramide (MCP; 30 mg/kg), produced ∼43.90% reduction (P < 0.05). At acute time point (3rd h), CS-HexFr decreased (P < 0.001) the concentration of 5HT and 5HIAA in the area postrema, brain stem and intestine, while at 18th h (delayed time point) CS-HexFr attenuated (P < 0.001) the upsurge of 5HT caused by cisplatin in the brain stem and intestine and dopamine in the area postrema. CS-HexFr treatment alone did not alter the basal neurotransmitters and their metabolites in the brain areas and intestine except 5HIAA and HVA, which were decreased significantly. In conclusion the anti-emetic effect of CS-HexFr is mediated by anti-serotonergic and anti-dopaminergic components in a blended manner at the two different time points, i.e., 3rd and 18th h in pigeons.